Arsenite and cadmium(II) as probes of glucocorticoid receptor structure and function. - S. Stoney Simons; Pradip K. Chakraborti; Alice Cavanaugh (1990)
Low concentrations of arsenite, but not arsenate, and Cd2+ blocked steroid binding to the glucocorticoid receptors of HTC cells. Inhibition by arsenite was faster and occurred at lower concentrations than for Cd2+. Half-maximal inhibition of [3H]dexamethasone binding was seen after a 30-min preincubation with approximately 7 microM arsenite. The effect of arsenite and of Cd2+ appears to be mediated by a reaction with vicinal dithiols of the receptor as shown by (a) the reversal of arsenite inhibition by much lower concentrations of dithiothreitol (approximately 0.1 mM) than of beta-mercaptoethanol (approximately 10 mM); (b) the ability of both arsenite and Cd2+ to block [3H]dexamethasone 21-mesylate labeling of receptors but not of other thiol-containing proteins; and (c) the known selectivity of arsenite and of Cd2+ for reactions with vicinal dithiols. Arsenite forms a tight complex with these vicinal dithiols since the removal of loosely associated arsenite by gel exclusion chromatography did not reverse the inhibition of steroid binding. The effect of other ions on steroid binding was also examined. Half-maximal inhibition of binding occurred with approximately 5 microM selenite, whereas up to 300 microM Zn2+ was without effect. Much higher concentrations of arsenite were required for effects on unactivated and activated complexes. Arsenite slowly induced a loss of unactivated complexes but rapidly inhibited a portion of the DNA binding of activated complexes. Any effect on activation occurred at arsenite concentrations equal to or higher than those that inhibited DNA binding. In contrast, Cd2+ concentrations similar to those that block steroid binding caused a biphasic loss of unactivated complexes and a marginal loss of activated complexes. This is the first report of effects of arsenite on glucocorticoid receptors. These results confirm directly our earlier hypothesis that steroid binding to rat glucocorticoid receptors involves a vicinal dithiol (Miller, N. R., and Simons, S. S., Jr. (1988) J. Biol. Chem. 263, 15217-15225) and show that arsenite is a potent new reagent for probing receptor structure and function.